Russian Policy Towards The Central Asian Republics (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The subject of this study revolves around Russian policy towards the Central Asian republics, where Russia has sought since the beginning of the third millennium to adopt a strategy with the goal of regaining control over these republics independent of the Soviet Union, as it falls within the Russian geopolitical sphere, and therefore is an important region to ensure Russian national security interests.                                                                Accordingly, the aim of this study revolves around a basic idea, which is how the Russian Federation can regain control over the independent republics in Central Asia, in light of internal challenges and the aspirations of regional and international powers in this important geopolitical field, and how Russian capabilities can be used to create a field Geopolitical safe.